Islam and Christianity at Rumah Gadang: The Household Characteristics of Minangnese Interfaith Marriage - Azhari Akmal Tarigan; Jufri Naldo; Syahrial Arif Hutagalung; Mohammad Reevany Bustami (JURIS (Jurnal Ilmiah Syariah), 2024)
This study discusses the Islam and Christianity at Rumah Gadang: Characteristics of Minangnese interfaith marriage in Padang, Yogyakarta, and Salatiga. Minangnese households in these three cities are unique because they have two different beliefs. Despite this, their domestic life continues to be harmonious, and no conflicts based on religious beliefs exist. The research setting was carried out in three cities in Indonesia: Padang, Yogyakarta, and Salatiga. This research explains the process of interfaith marriage for Minangnese who live outside the Minangkabau administrative area. It also describes factors that make their household life harmonious even though they have two different beliefs. Then, it explains the implications of the household life of Minangnese interfaith marriages outside the Minangkabau region, namely in Padang, Yogyakarta, and Salatiga. The research method used is qualitative, using a sociology of religion approach. The informants interviewed were Minang people who were married to Christian partners and Minang figures who lived in the research area. Meanwhile, respondents were taken randomly from residents living around the research object. This research found that the household characteristics of Minangnese interfaith marriage tend to be adaptive, tolerant, and Sufistic. This study claims that religion, which has been accused of being the source of conflict and divorce in the household, is not valid. This can be seen from the social interactions of couples of interfaith marriage who live in harmony, peace, and harmony